Identification and Development of Innovative Village in Banyumas Regency - Dian Purnomo Jati; Agus Suroso; Lusi Suwandari (EKO-REGIONAL, 2017)
The concept of innovative village initiated by Central Java Provincial Government contains the essence of utilization of village resources in a new way based on science, technology, and local wisdom for community welfare, village progress and improved living standards by involving all elements of the village. The research aimed to explore the characteristics of villages in Banyumas Regency that potentially served as an innovative village. The research phase began with focus group discussions to assess the potential of villages using rapid assessment and quantitative analysis of the Analytical Hierarchy Process. The discussion resulted in a list of 22 villages that were screened out through rapid assessment into 7 villages. The results of the focused group discussion also resulted in eight dimensions used as an instrument to select innovative village, namely: 1) empowerment of village potentials innovatively, 2) support of institutional system and village infrastructure, 3) capacity and commitment of rural apparatus, 4) technological accessibility by the community, 5) community participation, 6) tourism potential, 7) agricultural / plantation / forestry potential, and 8) livestock / fishery potential. The results of paired comparisons using AHP selected Kalisari village at Cilongok sub-district as an innovative village. Field surveys, observations and in-depth interviews were conducted in Kalisari village with respondents of village communities, village apparatuses, and district government agencies.Keywords: Model, Village, Innovative, Kalisari, Potency.